2018
DOI: 10.1021/acs.cgd.7b01330
|View full text |Cite
|
Sign up to set email alerts
|

A Kinetic Model for Hydroxyapatite Precipitation in Mineralizing Solutions

Abstract: Numerous studies have shown that there is an amorphous calcium phosphate (ACP) phase preceding the precipitation of crystalline hydroxyapatite (HA) in calcium phosphate solutions. It has also been shown that the addition of magnesium to the solutions has a stabilizing effect by inhibiting the transformation of ACP to HA. The stabilizing effect of Mg2+ is attributed to the stronger bonds between water molecules and the magnesium ions adsorbed on the surface of the ACP particles, making it harder for them to deh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…The incorporated Mg in ACP was proportional to the total added Mg in the initial solutions (Figure S5). This proportional relationship has also been noted and reported in Boskey et al’s work and Ding et al’s work for Mg/Ca ratio (for initial solutions) ranging up to 0.6. After the phase transformation of ACP, the final HAP crystallites contained much less Mg (about two-fifths of Mg remained after crystallization, i.e., the exclusion ratio is about three-fifths) (Figure S5).…”
Section: Resultssupporting
confidence: 85%
“…The incorporated Mg in ACP was proportional to the total added Mg in the initial solutions (Figure S5). This proportional relationship has also been noted and reported in Boskey et al’s work and Ding et al’s work for Mg/Ca ratio (for initial solutions) ranging up to 0.6. After the phase transformation of ACP, the final HAP crystallites contained much less Mg (about two-fifths of Mg remained after crystallization, i.e., the exclusion ratio is about three-fifths) (Figure S5).…”
Section: Resultssupporting
confidence: 85%
“…As mentioned above, ACP is a precursor phase that precedes the formation of crystalline hydroxyapatite in a supersaturated calcium phosphate solution. ACP particles consist of a random assembly of ion clusters, with a Ca/P molar ratio of about 1.2 compared to the ratio of 1.67 found in stoichiometric hydroxyapatite . The ratio of 1.91 determined for the studied LbL is higher than either of these values, suggesting that, in addition to calcium phosphate, calcium oxide (CaO) forms as well.…”
Section: Resultsmentioning
confidence: 80%
“…ACP particles consist of a random assembly of ion clusters, with a Ca/P molar ratio of about 1.2 compared to the ratio of 1.67 found in stoichiometric hydroxyapatite. 51 The ratio of 1.91 determined for the studied LbL is higher than either of these values, suggesting that, in addition to calcium phosphate, calcium oxide (CaO) is forming as well. Previous studies have demonstrated that higher Ca/P ratios induce increased osteoblast adhesion, 52 but can also lower osteoblast viability.…”
mentioning
confidence: 77%
“…As the calculations demonstrated, the overall decrease in pH can be explained by the formation of ion pairs that changed the ratio of free phosphate species toward a lower [HPO 4 2– ] content (see Supporting Information Figure S2). The fluctuations in pH before its stabilization has previously been attributed to the possible formation of unstable clusters and solids due to local areas of high supersaturation created by the addition of calcium solution, which then immediately dissociate to establish an equilibrium. , The drop of pH below the equilibrium value followed by its fast rebound supported a similar mechanism indicating formation of highly unstable solution species and/or solid upon fast addition of calcium (Figure A). Due to the slow dehydration rate of calcium ions compared to that of phosphate species, nonequilibrium complexes with a calcium deficiency can emerge in the system for a short time interval …”
Section: Resultsmentioning
confidence: 99%